Outcome-Based Education (OBE) Curriculum: Implementation in the Arabic Language and Literature Study Program - Chotimah, Dien Nur; Kirom, Makhiulil; Roziki, Khafid; Abidin, Munirul (Universitas Islam Negeri Raden Intan Lampung, 2025)
As higher education institutions transition toward competency-based frameworks, Outcome-Based Education (OBE) has emerged as a pivotal model for aligning curriculum with measurable learning outcomes. In the context of Islamic higher education, the integration of OBE remains a growing area of interest. This study explores the implementation of the Outcome-Based Education (OBE) curriculum in the Arabic Language and Literature Study Program at the Faculty of Humanities, Universitas Islam Negeri Maulana Malik Ibrahim Malang. It focuses on insights from the program coordinators and examines the challenges encountered during the implementation process. Employing a phenomenological approach, data were collected from primary sources, including the head and secretary of the study program, through direct observation and in-depth interviews. The data were analyzed using interpretative phenomenological analysis. The findings reveal that the implementation process involves several stages: curriculum review, dissemination of OBE policy to faculty and students, and ongoing monitoring and evaluation. Key challenges include faculty and student readiness to adopt new approaches, resistance to change, difficulties in accurately measuring learning outcomes, limited resources and facilities, and time constraints. To enhance the effectiveness of OBE implementation, it is recommended that institutions provide targeted professional development, improve infrastructure support, and promote a collaborative academic culture. Future research could explore cross-institutional comparisons and long-term impact assessments of OBE-based curriculum reforms.